The “Russian Law” in Georgia: Human Rights, Legal Certainty, and the Passions of the Georgian Lawmakers - Dimitry Gegenava; Tsisia Okropiridze; Ketevan Bakhtadze; Sandro-Giorgi Sarukhanishvili (Review of European and Comparative Law, 2025)
The article examines Georgia’s Law “On Transparency of Foreign Influence” (the “Russian Law”), analyzing its implications for fundamental rights and democratic governance within Georgia’s post-Soviet context. Through comparative analysis of the United States’ Foreign Agents Registration Act (FARA) and the Russian Federation’s Foreign Agents Laws (RFAL), the research demonstrates how Georgia’s legislation substantively aligns with the Russian rather than the American act, despite claims by its proponents. The study reveals how the Georgian legislation creates substantial barriers to civil socjety operations through mandatory registration requirements, intrusive monitoring mechanisms, and punitive financial sanctions. Drawing upon the European Court of Human Rights jurisprudence and the Venice Commission’s opinions, the analysis shows that while the law ostensibly pursues transparency objectives, its practical effect significantly impedes democratic development and Euro-Atlantic integration aspirations, potentially constituting a regression in Georgia’s post-Soviet democratic trajectory. The findings contribute to discourse on legal mechanisms for civil society regulation in emerging democracies, offering critical insights into how transparency frameworks can become instruments of institutional control. This investigation holds particular significance for understanding contemporary challenges to democratic consolidation in post-Soviet states and the complex interplay between legal frameworks and political transformation processes.